„Co było nie wróci?” – czyli Bułata Okudżawy nostalgiczne powroty do Rosji dekabrystów - Sucharski, Tadeusz (Studia Rossica Posnaniensia, 2019)
In the presented text I undertake the reflection on the forms of expressions of nostalgia in Bulat Okudzhava’s historical prose. His novel takes place in the first half of the nineteenth century, the times associated with the movement of the Decembrists. The writer really appreciated the Decembrists, but showed their era objectively or even critically because he saw the analogy between the past and his present.